Activated carbon cloth filled pipette tip for solid phase extraction of nickel(II), lead(II), cadmium(II), copper(II) and cobalt(II) as 1, 3, 4-thiadiazole-2, 5-dithiol chelates for ultra-trace detection by FAAS. Issue 2 (26th January 2018) - Habila, Mohamed A.; ALOthman, Zeid A.; Yilmaz, Erkan; Soylak, Mustafa
ABSTRACT: A solid phase extraction method is established for preconcentration of nickel, lead, cadmium, copper and cobalt using pipette tip solid phase extraction. The presented process was dependent on chelation of analytes with 1, 3, 4-thiadiazole-2, 5-dithiol, then allowing the solution to flow through an activated carbon cloth packed pipette tip. The adsorbed metal chelates on the surface of activated carbon cloth were eluted by 5 mL of 3 M HNO3 . The concentrations of nickel, lead, cadmium, copper and cobalt were detected using a flame atomic absorption spectrometer (FAAS). The pipette tip solid phase extraction exhibit a preconcentration factor of 120. The limit of detection values were 2.7, 1.7, 1.3, 2.0 and 2.9 µg L −1 for Ni(II), Pb(II), Cd(II), Cu(II) and Co(II), respectively. Validation of the method was checked by the analysis of TMDA-53.3 and TMDA-64.2 certified reference materials. The method was successfully applied for water and fertiliser samples.